The strategy of design and preparation for outstanding precipitation strengthened HEAs based on diffusion couple - Shun-Xin Zhang (Materials & Design, 2022)
Precipitation strengthened high entropy alloys (HEAs) have achieved wide attention competing to traditional alloys, due to excellent mechanical properties. Until recently, the composition design of precipitation strengthened HEAs mainly depends on individual calculation or cooking experiment. At this point in time, we proposed a new strategy to efficiently screen the composition range of solid solution for single-phase HEAs based on diffusion couple technique. Each new HEAs matrixes can be easily strengthened by nano-precipitates through subsequent aging heat-treatment. As an example of this reliable and universal approach, two brand-new Co22.8Cr19Fe23.5Ni24.7Cu5Ti5 and Co24Cr20.9Fe25.1Ni24Al3Ti3 HEAs, are discovered, prepared, and tested correspondingly, which exhibit outstanding strength-plasticity com binations far superior to those reported in the literatures. Their ultimate tensile strengths are 1281 MPa and 1339 MPa, respectively, with the elongation of 30% and 19%. In both alloys, the uniformly dispersed nano-precipitates γ′ with L12 ordered structure are observed to be coherent with the FCC matrix phase. The dominant deformation and strengthening mechanisms of both alloys are planar dislocations and stacking faults. The design strategy is not only applicable to the present work but also introduces new thoughts for the rapid development of other new precipitation strengthened HEAs.